Dampak Pembangunan Wisata Danau Perintis Pada Masyarakat Sekitar - Badjuka, Alexander H.; Pakaya, Sri Rahayu; Saridin, Nur Rustiya; Abdullah, Abdul Hafit; Hilahapa, Raihan Alamsyah (JPS: Journal of Publicness Studies, 2026)
Tourism development is one of the important sectors in supporting regional economic growth and improving community welfare. The development of Perintis Lake tourism is expected to create positive impacts for local communities, especially in economic, social, and environmental aspects. This study aims to examine the impacts of Perintis Lake tourism development on the surrounding community. The research applies a descriptive qualitative method through observation, interviews, and literature studies from journals and books published within the last eight years. The findings indicate that tourism development at Perintis Lake has contributed positively to increasing local income, creating employment opportunities, encouraging the growth of micro and small businesses, and improving village infrastructure. Nevertheless, several negative impacts were also identified, including environmental pollution, traffic congestion during holidays, and shifts in social behavior among local residents. Most community members support the tourism development because it improves economic conditions, although they expect better environmental management and stronger community empowerment from the government. Therefore, tourism development at Perintis Lake significantly contributes to community welfare, but sustainable management is still required to reduce negative effects.